Epidemiology of food allergy in Latin America (2015)
ABSTRACT: Food allergy is growing worldwide at an alarming rate. A group of eight foods account for over 90% of the reactions in Europe and the United States. However, little is known about the frequency of sensitization to these foods in Latin American, and if other native foods from this region are an important source of sensitization. The objective of this review was to analyse the epidemiological studies in Latin America about food allergy and to compare them with the studies in the United States and Europe.